Measurement of striking impact kinetics via inertial modelling and accelerometry - Lenetsky, S.; Nates, R. J.; Brughelli, M.; Schoustra, A. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Striking impact has teen explored repeatedly in combat sports. The majority of methods used in the literature require intricate equipment. This study implemented a novel and simple method of measuring impact kinetics using a common, commercially available striking bag. Impulse and peak force of impacts were determined, with reliability and validity statistics obtained from multiple impacts with a custom ballistic pendulum. Test-retest reliability calculations determined that all measures had acceptable reliability (CVI less than/ equal to 2.4%). Using linear regression modelling, the coefficient of determination scores displayed a good fit for the model (R exponent 2 greater than / equal to 0.96) when plotted with a spectrum of pendulum masses. This novel method represents a reliable and valid approach to measuring striking impact kinetics which is easily adaptable to any type of hanging striking target.